A NATIONAL, MULTICENTER, SECONDARY DATA USE STUDY EVALUATING EFFICACY AND RETENTION OF FIRST-LINE BIOLOGIC TREATMENT WITH TOCILIZUMAB IN PATIENTS WITH RHEUMATOID ARTHRITIS IN REAL-LIFE SETTING FROM TURKBIO REGISTRY - Yazici, A.; Isik, O. Ozdemir; Dalkilic, E.; Koca, S. S.; Pehlivan, Y.; Senel, S.; Onen, F. (Elsevier, 2021)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 02-05, 2021 -- ELECTR NETWORK